Management of bladder cancer in older patients: Position paper of a SIOG Task Force. Issue 7 (September 2020) - Mottet, Nicolas; Ribal, Maria J.; Boyle, Helen; De Santis, Maria; Caillet, Philippe; Choudhury, Ananya; Garg, Tullika; Nielsen, Matthew; Wüthrich, Patrick; Gust, Kilian M.; Shariat, Shahrokh F.; Gakis, Georgios
Abstract: Median age at bladder cancer (BC) diagnosis is older than for other major tumours. Age should not determine treatment, and patients should be fully involved in decisions. Patients should be screened with Mini-Cog™ for cognitive impairment and the G8 to ascertain need for comprehensive geriatric assessment. In non-muscle invasive disease, older adult patients should have standard therapy. Age does not contraindicate intravesical therapy. Independent of age and fitness, patients with muscle-invasive BC should have at least cross-sectional imaging. Data suggest extensive undertreatment in older adult patients, leading to poor outcomes. Standard treatment for a fit patient differs between countries. Radical cystectomy and trimodality therapy are first-line options. Radical cystectomy patients should be referred to an experienced centre and prehabilitation is mandatory. Older adult patients should be considered for neoadjuvant and adjuvant therapy, according to guidelines. In urinary diversion, avoiding bowel surgery for reconstruction of the lower urinary tract significantly reduces complications. If a patient is unfit for or refuses standard treatment, RT alone, or TURBT in selected cases should be considered. In metastatic BC, older adult patients should receive standard systemic therapy, depending on fitness for cisplatin and prognosis. Efficacy and tolerability of immunotherapy (IO) appears similar to younger patients. Second line IO is standard in platinum pre-treated patients, with benefit and tolerability in the older adult similar to younger patients. The toxicity profile seems to favour IO in the older adult but more data are needed. Patients progressing on IO may respond to further systemic treatment. In metastatic disease, palliative care should begin early. Highlights: Of the major tumours, patients with bladder cancer (BC) are the oldest at diagnosis. Treatment should be determined by fitness, prognosis and patient preference. Undertreating non-invasive BC risks poor outcome; intravesical therapy is an option. In invasive BC, consider radical cystectomy with prehab and trimodality therapy. In advanced disease consider cisplatin in the fit. Immunotherapy could have a role.